2020
DOI: 10.1007/s10618-019-00669-5
|View full text |Cite
|
Sign up to set email alerts
|

Parameterized low-rank binary matrix approximation

Abstract: We provide a number of algorithmic results for the following family of problems: For a given binary m × n matrix A and integer k, decide whether there is a "simple" binary matrix B which differs from A in at most k entries. For an integer r, the "simplicity" of B is characterized as follows.• Binary r-Means: Matrix B has at most r different columns. This problem is known to be NP-complete already for r = 2. We show that the problem is solvable in time 2 O(k log k) · (nm) O(1) and thus is fixed-parameter tracta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 72 publications
1
29
0
Order By: Relevance
“…Let us now look at algorithms with theoretical guarantees. Gramm et al (2008) and Fomin et al (2020) showed that an exact solution for BMF can be computed in time 2 2 O(k) (mn) O(1) , thus matching the above lower bound.…”
Section: Theoretical Algorithmssupporting
confidence: 59%
“…Let us now look at algorithms with theoretical guarantees. Gramm et al (2008) and Fomin et al (2020) showed that an exact solution for BMF can be computed in time 2 2 O(k) (mn) O(1) , thus matching the above lower bound.…”
Section: Theoretical Algorithmssupporting
confidence: 59%
“…Related results are also presented in very recent works which investigated the complexity of different matrix editing and clustering problems from the parameterized and approximation perspectives (Fomin, Golovach, and Panolan 2018;Fomin et al 2019;Eiben et al 2019). All of these papers except for the last one are concerned with the complete data setting.…”
Section: Introductionmentioning
confidence: 90%
“…Other works which investigate the theoretical aspects of the BMF problem have also been done recently [21], [38]- [40]. A method to solve the joint BMF problems, meaning to find Boolean factors shared by two Boolean data matrices, is also studied in [41].…”
Section: Related Workmentioning
confidence: 99%